Pemberdayaan Lansia Melalui Edukasi Metode Balance, Eyes, Face, Arm, Speech And Time Sebagai Self Awarness Terhadap Deteksi Dini Stroke - Suyasa, I Gede Putu Darma; Agustini , Ni Luh Putu Inca Buntari; Sani, Ari Wina; Wahyuni, Ni Wayan Sri; Wangi, Ni Luh Putu Ayu Puspita; Putra, Kadek Andika Dwi (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Hypertension is a common condition in primary health care, affecting approximately 25% of the adult population and more than 50% of those aged over 65 years. As the "silent killer of hypertension", it can cause stroke, which is a major cause of morbidity and mortality worldwide. This study aims to detect early signs of stroke using the BE-FAST method in the elderly in Karangasem, Bali, and to spread the effectiveness of this method in reducing the risk of stroke. Method: This community-based education program uses the POAC (Planning, Organizing, Actuating and Controlling) approach. A total of 79 elderly participants were recruited and underwent health examinations, including blood pressure measurements and the BE-FAST screening test. The BE-FAST method assesses balance, eyes, face, arms, speech, and timing to identify early signs of stroke. Results: The results showed that 55.7% of participants had hypertension, and 67.1% had difficulty moving their legs and arms on one side of their body. Additionally, 36.7% had difficulty opening their eyes or experienced vision problems, and 32.9% experienced facial weakness or numbness. The BE-FAST method is effective in detecting early signs of stroke, with a sensitivity of 92%. Conclusion: This study highlights the importance of early detection of stroke using the BE-FAST method in the elderly population. The research results show that this method is effective in identifying early signs of stroke and can be easily taught and applied in the community. Application of this method can reduce the risk of stroke and associated morbidity and mortality.